Copyright © 2016 EDAM - (:unkn) unknown (My University, 2016)
0

The concept of self-efficacy, which is an important variable in the teaching process, and how it reflects on teaching have recently been the focus of attention. Therefore, this study deals with the relationship between the science-teaching self-efficacy beliefs of prospective science teachers and their teaching practices. It was conducted with four prospective science teachers who were in their final year at a state university. The teaching processes of prospective science teachers, all of whom had different levels of science teaching selfefficacy beliefs, were detected using the case study, a qualitative research method. Observations, interviews, and documents were used as data collection tools. The obtained data were analyzed through the method of content analysis. According to the findings, although the prospective science teachers were observed to have different levels of self-efficacy belief, they agreed that the student-centered approach was more suitable for students, especially in terms of the teaching process. However, they reflected this differently in their practices. Contrary to expectation, it was generally confirmed that teachers with high-levels of self-efficacy might perform their teaching practices less efficiently in some situations, while teachers with low-level of self-efficacy might perform their teaching practices more efficiently
The Teaching Processes of Prospective Science Teachers with Different Levels of Science-Teaching Self-Efficacy Belief
Keywords: Eğitim, Eğitim Araştırmaları